Comparison of direct and port injection of methanol in a RCCI engine using diesel and biodiesel as high reactivity fuels - Altun, Sehmus; Firat, Mujdat; Varol, Yasin; Okcu, Mutlu (Elsevier, 2023)
In this work, methanol dual-direct injection (DI2 mode) was compared with the port injection of methanol (RCCI mode) when biodiesel and diesel fuel were employed as HRFs (High Reactivity Fuels). This study presents an innovative dual-direct injection strategy as an alternative method to the commonly utilized port injection strategy in RCCI engines, and evaluates its impact on both engine performance and pollutant emissions. The engine was operated at a constant speed of 2400 rpm by a single-cylinder diesel research engine, and BMEP of 1.57, 3.15, and 4.72 bar (20 %, 40 %, and 60 % of max torque) with methanol was injected using both the DI2 and RCCI modes while diesel fuel and biodiesel were injected directly. In reactivity-controlled compression ignition (RCCI) mode, NOx emissions were reduced by 60 % and 62 % for diesel fuel and biodiesel, respectively, while the reduction accounted as 92 % and 80 % in smoke opacity. However, CO and unburned HC emissions were measured as higher for advanced modes than conventional mode using diesel fuel and biodiesel. According to experimental results obtained for DI2, unburned HC and CO emissions were reduced (up to 63 % and 22 %) when compared with RCCI mode. In addition, for DI2, NOx emissions were slightly higher than in RCCI mode, mainly due to the high injection pressure (50 bar) of DI2 mode. In comparison to conventional diesel injection (CDI), cylinder pressure and heat release rate (HRR) decreased as the premixed ratio (Rp) increased at 20 % load, while cylinder pressure and HRR increased with load and Rp increased. In both diesel and biodiesel experiments, ignition delay increased as Rp increased. The ignition delay was found to be longer in RCCI mode than in DI2 mode. It was concluded that DI2 was a beneficial way to control inefficient combustion during RCCI operation fuelled by diesel fuel and biodiesel.
Keywords: RCCI; Methanol; Dual direct injection (DI 2 ); Combustion and emissions; Biodiesel